1988
DOI: 10.1161/01.str.19.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of stroke in a nonhuman primate model of cerebrovascular disease.

Abstract: A relation between hypertension, atherosclerosis, and stroke is well documented in humans. We report a similar relation in two hypertensive cynomolgus monkeys with severe cerebral atherosclerosis. In our primate model hypertension is induced by surgical coarctation of the aorta. These monkeys, when fed an atherogenic diet, develop severe cerebrovascular atherosclerosis. In this setting two monkeys developed spontaneous cerebral hemispheric strokes that occurred during treatment of hypertension. Since the strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…There is increased insudation of fibrinogen and LDL‐cholesterol in the subendothelial spaces82 consistent with human pathological findings 83, 84. In cynomolgus monkeys, hypertension induced by surgical thoracic aorta coarctation and hypercholesterolemic diet for 12 months induces ICAD85 with associated ischemic strokes 86. Infiltration of lipid‐laden foam cells and lipid droplet–filled smooth muscle cells have been described in the basilar artery in this model 87.…”
Section: Existing Experimental Modelssupporting
confidence: 85%
“…There is increased insudation of fibrinogen and LDL‐cholesterol in the subendothelial spaces82 consistent with human pathological findings 83, 84. In cynomolgus monkeys, hypertension induced by surgical thoracic aorta coarctation and hypercholesterolemic diet for 12 months induces ICAD85 with associated ischemic strokes 86. Infiltration of lipid‐laden foam cells and lipid droplet–filled smooth muscle cells have been described in the basilar artery in this model 87.…”
Section: Existing Experimental Modelssupporting
confidence: 85%
“…To date, no stroke studies seem to have been undertaken in hypertensive transgenic rats expressing an extra copy of the renin gene (Wagner et al , 1997). Ischemic stroke has been induced in Cynomolgus monkeys made hypertensive by surgical coarctation of the aorta in animals fed an atherogenic diet (Prusty et al , 1988), but this would not seem to be a practical model for widespread use.…”
Section: Effects Of Comorbidities On Outcomementioning
confidence: 99%
“…In contrast to atherosclerosis found at peripheral regions, cerebral atherosclerosis appears particularly related to hypertension (Sadoshima et al, 1980). In addition, high fat diet and hypertension induced by surgical treatment caused intracranial atherosclerosis in cynomolgus monkeys (Prusty et al, 1988;Hollander et al, 1993) and rabbits (Kato et al, 1991). Unfortunately, we could not reliably measure the blood pressure under unanesthetized conditions in our study, because their blood pressure was found to be highly variable during our measurement period.…”
Section: Discussionmentioning
confidence: 80%
“…However, a high fat diet in combination with surgical interventions, such as a vasectomy (Alexander and Clarkson, 1978) or experimental hypertension by coarcting the thoracic aorta (Prusty et al, 1988), has been shown to effectively induce intracranial atherosclerosis in nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%